2013
DOI: 10.4025/actasciagron.v35i4.17489
|View full text |Cite
|
Sign up to set email alerts
|

<b>Response to the selection in the 11<sup>th</sup> cycle of reciprocal recurrent selection among full-sib families of maize</b> - doi: 10.4025/actasciagron.v35i4.17489

Abstract: ABSTRACT. The continuous gains in cycles of recurrent selection have raised disagreement among researchers. Two hundred and forty-two full-sib families were obtained from CIMMYT and Piranão populations and evaluated in a simple lattice design in two environments to estimate the response to selection in the 11 th cycle of the UENF reciprocal recurrent selection program. No genotype x environment interaction was observed for most of the traits evaluated, indicating that a single recurrent selection program can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 24 publications
2
26
1
7
Order By: Relevance
“…In the literature, there are reports of gain achieved with long term RRS with various selection cycles. In these cases, the average gain ranged from 7 to 13% per cycle (Santos et al, 2007;Hallauer and Carena, 2012;Berilli et al, 2013), which is lower than the values reported in the present study.…”
Section: Resultscontrasting
confidence: 55%
“…In the literature, there are reports of gain achieved with long term RRS with various selection cycles. In these cases, the average gain ranged from 7 to 13% per cycle (Santos et al, 2007;Hallauer and Carena, 2012;Berilli et al, 2013), which is lower than the values reported in the present study.…”
Section: Resultscontrasting
confidence: 55%
“…The oscillations in gains between cycles and the coefficient of determination of only 11 % explain the absence of detected total gain in DF (Figure 2). The use of alternative selection criteria, such as the selection index, might have contributed to simultaneous gains in the different traits (Smith et al, 1981;Berilli et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…These coefficients of variation demonstrate acceptable experimental accuracy for all traits. Berilli et al (2013) obtained coefficient of experimental variation and heritability of 20% and 56%, respectively, for yield in the 11th reciprocal recurrent selection cycle among corn full-sib families. Faria et al (2008) evaluated the effectiveness of reciprocal recurrent selection in popcorn hybrids, and obtained coefficient of experimental variation (CV e ) and heritability (h 2 ) of 20.90% and 50.37% for yield, respectively.…”
Section: Analysis Of Variance and Genetic Parametersmentioning
confidence: 99%